The domestic chick as an animal model of autism spectrum disorder: building adaptive social perceptions through prenatally formed predispositions - Matsushima, Toshiya; Izumi, Takeshi; Vallortigara, Giorgio (Frontiers in Neuroscience, 2024)
Equipped with an early social predisposition immediately post-birth, humans typically form associations with mothers and other family members through exposure learning, canalized by a prenatally formed predisposition of visual preference to biological motion, face configuration, and other cues of animacy. If impaired, reduced preferences can lead to social interaction impairments such as autism spectrum disorder (ASD) via misguided canalization. Despite being taxonomically distant, domestic chicks could also follow a homologous developmental trajectory toward adaptive socialization through imprinting, which is guided via predisposed preferences similar to those of humans, thereby suggesting that chicks are a valid animal model of ASD. In addition to the phenotypic similarities in predisposition with human newborns, accumulating evidence on the responsible molecular mechanisms suggests the construct validity of the chick model. Considering the recent progress in the evo-devo studies in vertebrates, we reviewed the advantages and limitations of the chick model of developmental mental diseases in humans.